Beobachtungen zum Artikelgebrauch durch Lerner des Deutschen (L1: Französisch und Italienisch) - Roncoroni, Tiziana (Linguistik Online, 2018)
This explorative study sheds light on article usage in German academic texts by French and Italian university (including Ph. D.) students. Given the differences between and among Romance and Germanic language systems, one might expect deviations in article usage in L2 German; in particular, speakers of Romance languages would seem likely to overgeneralise articles in their German language production. Contrary to these hypotheses, the corpora of learner varieties investigated in the present paper do not show evidence of overrepresentation and overgeneralisation of German articles, not even in generic sentences. In fact, articles tend to be underrepresented, as L2 learners often omit articles that are required in L1 German. Potential explanations of these findings are provided, giving rise to further research questions and desiderata. The latter include empirical studies on L1 German article usage in bilingual areas such as South Tirol, the use of articles in translations, and comparisons of article usage between L1 German and the L2 varieties of learners whose L1 does not have grammaticalised articles. Such studies should apply qualitative (i. e. semantic and pragmatic) as well as quantitative methods.